A review of individual factors on knowledge sharing: Evidence from the empirical literature - Shehab S.; Rahim R.E.A.; Daud S. (Science Publishing Corporation Inc, 2023)
Knowledge sharing is considered to be an essential concept and a determinant of success regarding knowledge management. The current paper reviews the most relevant quantitative studies, within the context of individual-level knowledge sharing. The main aim of this paper is to identify the relevant individual factors that influence knowledge sharing. Furthermore, it seeks to identify relevant theories, previously used in literature, that communicate a theoretical understanding of individual levels of knowledge sharing. The researchers searched through five well-known databases using a combination of keywords related to the study context. By applying filtration procedures to the articles gathered from the selected databases, the literature survey revealed 31 most relevant articles. As a result of reviewing the selected articles, it has been indicated that the factors that most affect knowledge sharing include trust, reciprocity, self-efficacy, altruism, and reputation. These factors, studied through different contexts, have been found to significantly affect the behavior of individuals in terms of sharing knowledge. Furthermore, it has been found that the social exchange theory has been repeatedly used. It has been concluded that the resulted antecedents may influence the knowledge sharing of individuals and consider these factors by the decision makers will motivate the individual's intention to knowledge sharing. 2018 Authors.